2022
DOI: 10.3390/pathogens11070752
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glaesserella parasuis and Differentiation of Its 15 Serovars Using High-Resolution Melting Assays

Abstract: Glaesserella parasuis is the etiological agent of Glässer’s disease, which is associated with polyserositis and arthritis and has a significant impact on the economy of the pig production industry. For the optimal surveillance of this pathogen, as well as for the investigation of G. parasuis-associated diseases, it is crucial to identify G. parasuis at the serovar level. In this work, we designed and developed new high-resolution melting (HRM) approaches, namely, the species-specific GPS-HRM1 and two serovar-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The detection of virulent vtaA in Malaysia isolates belonging to OmpP2 genetic type I, and nonvirulent vtaA in isolates belonging to OmpP2 genetic type II, seems to be parallel. However, mapping information from previous literature [ 41 ] showed that strains from genetic type II, such as strain H465 and SW124 of Germany, also possess virulent vtaA , even though all strains in the genetic type I were found to possess virulent vtaA . This may indicate that the two genes are not directly related, but when combined, both may yield more severe clinical infections; this is worth being studied further.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of virulent vtaA in Malaysia isolates belonging to OmpP2 genetic type I, and nonvirulent vtaA in isolates belonging to OmpP2 genetic type II, seems to be parallel. However, mapping information from previous literature [ 41 ] showed that strains from genetic type II, such as strain H465 and SW124 of Germany, also possess virulent vtaA , even though all strains in the genetic type I were found to possess virulent vtaA . This may indicate that the two genes are not directly related, but when combined, both may yield more severe clinical infections; this is worth being studied further.…”
Section: Discussionmentioning
confidence: 99%
“… a Serovars determined by multiplex PCR (Howell et al, 2015 ) and high‐resolution melting PCR assay (Scherrer et al, 2022 ). b Virulence determined by leader sequence PCR (Galofré‐Milà et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“… a Serovars determined by multiplex PCR (Howell et al, 2015 ) and high‐resolution melting PCR assay (Scherrer et al, 2022 ). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations